2017
DOI: 10.1021/acs.molpharmaceut.6b00795
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Oxide Nanoparticle–Poly I:C RNA Complexes: Implication as Therapeutics against Experimental Melanoma

Abstract: There is current interest in harnessing the combined anticancer and immunological effect of nanoparticles (NPs) and RNA. Here, we evaluate the bioactivity of poly I:C (pIC) RNA, bound to anticancer zinc oxide NP (ZnO-NP) against melanoma. Direct RNA association to unfunctionalized ZnO-NP is shown by observing change in size, zeta potential, and absorption/fluorescence spectra upon complexation. RNA corona was visualized by transmission electron microscopy (TEM) for the first time. Binding constant (K = 1.6-2.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 104 publications
4
40
0
Order By: Relevance
“…In a relatively recent report we reviewed the molecular cell immunology of the metastatic tumor niche and the cytokines which are thought to regulate it [3]. We previously characterized the interaction of poly I:C to ZnO to form poly I:C-ZnO nano-complexes [34] and consistent with another recent study [4], demonstrated inhibition of experimental melanoma in B16F10-BALB/c mice by poly I:C-ZnO nano-complexes relative to ZnO NP or poly I:C controls [13]. Analysis of the poly I:C-ZnO-treated tumors relative to control mice receiving sham PBS intratumoral injection in this immuno-competent B16F10-BALB/c mouse model demonstrates significant antitumor cytokine response (Table 1).…”
Section: In Vivo Direct Intratumoral Injection Modelsupporting
confidence: 71%
See 2 more Smart Citations
“…In a relatively recent report we reviewed the molecular cell immunology of the metastatic tumor niche and the cytokines which are thought to regulate it [3]. We previously characterized the interaction of poly I:C to ZnO to form poly I:C-ZnO nano-complexes [34] and consistent with another recent study [4], demonstrated inhibition of experimental melanoma in B16F10-BALB/c mice by poly I:C-ZnO nano-complexes relative to ZnO NP or poly I:C controls [13]. Analysis of the poly I:C-ZnO-treated tumors relative to control mice receiving sham PBS intratumoral injection in this immuno-competent B16F10-BALB/c mouse model demonstrates significant antitumor cytokine response (Table 1).…”
Section: In Vivo Direct Intratumoral Injection Modelsupporting
confidence: 71%
“…In this experiment we compared ZnO to nickel oxide (NiO) or magnesium oxide (MgO) NP, where our group and one other have shown that these compositions may be able to functionally load protein or protein-RNA complexes onto their surfaces [32][33][34], making their baseline immunogenicity of great interest as a potential carrier of peptide/protein or RNA-based immuno-therapeutics. Based on earlier dose ranging experiments and our experience, splenocytes were incubated with a 20 µg/mL dose of ZnO, MgO, or NiO NP [9,10,13,31,33]. Splenocytes were isolated from the mouse spleen, exposed to concentrations and stained with propidium iodide (PI) and the cell populations separated and counted by flow cytometry (Figure 2).…”
Section: Ex Vivo Splenocyte Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro cytotoxicity test of precursors of hydrogels, fillers of SNPs and H 9.0 hydrogel were assayed using a CCK‐8 assay with L929 fibroblasts cells over 7 days . Results were shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Significant results in terms of cytokine production and positive therapeutic outcome in mice have also been recorded with nanoparticle-mediated IL-12 gene therapy [16]. In addition, nanoparticle encapsulation has been reported for IL-2 [1820], IL-15 [21], IL-10 siRNA [22], GM-CSF [23, 24], and the toll-like receptor (TLR) agonists CpG oligodeoxynucleotides (CpG-ODN) [2527] and Poly I:C [28, 29], with positive outcomes in mouse models (Table 1). All these studies collectively confirmed the previous assumption that nanoparticle formulations are safer and induce better therapeutic effects than their free-soluble counterparts due to controlled local administration and higher concentration at the tumor site in virtue of the EPR effect.…”
Section: Immunomodulatory Drug Deliverymentioning
confidence: 99%